L’approccio teorico e operativo dell'Intelligenza Territoriale (IT) come risposta alle sfide della globalizzazione - Pierpaolo Donati (Culture e Studi del Sociale)
The paper deals with the issue of the development of Territorial Intelligence (TI) as influ-enced by the way in which individual and collective agents/actors understand and practice social networking (the ‘culture of social networks’). TI can be viewed basically as a re-sponse to the challenges of globalization, in so far as globalization redefines the territorial borders of all political-administrative systems and brings about the ‘reticularization’ of the whole society. Donati argues that we must elaborate a general framework which can allow us to analyze the TI as a networking system whose success or failure depends on how it works out the culture of social networks in terms of production and/or consumption of so-cial capital in its different forms (primary, secondary, generalized). The building of local welfare systems can provide more or less social cohesion depending on the fact that the cul-ture of social networking be able to produce common goods as relational goods stemming from an emergentist dynamics of social capital.